Kingdom of the Netherlands-Netherlands : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents an assessment of financial system stability in the Netherlands. The country is home to a global systemically important bank and a global systemically important insurer. The banking system comprises half of the financial sector and is concentrated in four domestic banks. Major reforms, driven by the European Union and global developments, have significantly strengthened financial sector oversight. The authorities' response to the global financial crisis was far-reaching and addressed many deficiencies. The Single Supervisory Mechanism has enhanced bank supervision, as have strengthened capital and liquidity regulations. Insurance supervision is also stricter thanks to Solvency II, and there is a new framework for the pension sector.